Penal Policy (’Dandniti’) in Ancient India and its Relevance in Contemporary Times - Naik, Revati (Tribhuvan University Law Journal, 2025)
Criminal law of any country is essentially concerned with the answers of certain questions such as to what is the essential quality of crime as distinguished from other branches, how is the crime to be combated either by applying the defensive reaction to the crime or the criminal, is the reaction to be by way of punishment or by way of measures of security for social defence and how the application of the punishment is to be individualised and on the basis of what principles and methods? The penology as a branch of criminal law is a multi-disciplinary faculty which aims to study and evaluate the application of penal sanctions to wrongdoers. It broadly explains the justification, characteristics and effectiveness of punishment in its various forms. In law, crime is perceived as a wrong against the society and the offender, state victim and society are considered as the stakeholders. Punishment is the expression of social values as well as instrumental means to a clinical penological end. The judge while inflicting the sentence has to balance the conflicting interests of victim, offender and society and this requires the effective penal policy. The progress of mankind and processes such as globalisation and modernisation exercise considerable influence on the penal policies. It can also be said that the penal policy of the society can be considered as an indicator of quality of civilisation attained by it. The purpose of this article is to explore the ancient penal policy and to find out as to how far ancient penal policy is relevant and can be useful in modern times in the context of current approaches in criminal law such as restorative justice and different types of punishments such as community service.